Designing Inservlce Education for Extension Personnel: The Role of Learning Styles In Computer Training Programs - Sung·Youl Park; Julia Gamon (Journal of Applied Communications, 1996)
The primary purpose of this survey research study was to identify the learning styles of Iowa State University Extension Service Personnel and to investigate relationships between learning styles and opinions toward computer training and support.